Mod en teori om kausale hukommelsesprocesser: præliminære bemærkninger - Christensen, Mathias (Studier i Pædagogisk Filosofi, 2018)
This paper argues for a theory of memory that I have coined “the theory of causal memory processes”. The central claim of the paper is that it is more empirically sound to construct theories of memory in accordance with the theory of causal processes rather than in accordance with causality as regulation. In order to put this claim forward I will, first, describe what kind of function causality serves in philosophical theories of memory. Secondly, I will show that regularity theories of causation is dominant in the causal theories of memory. Thirdly, I will account for the theory of causal processes. Lastly, I will sketch a definition of the theory of causal memory processes.